2020
DOI: 10.1371/journal.pone.0237403
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent regulation of horizontal cell fate by Onecut family of transcription factors

Abstract: Genome duplication leads to an emergence of gene paralogs that are essentially free to undergo the process of neofunctionalization, subfunctionalization or degeneration (gene loss). Onecut1 (Oc1) and Onecut2 (Oc2) transcription factors, encoded by paralogous genes in mammals, are expressed in precursors of horizontal cells (HCs), retinal ganglion cells and cone photoreceptors. Previous studies have shown that ablation of either Oc1 or Oc2 gene in the mouse retina results in a decreased number of HCs, while sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Additive functions lead to a gradually worsened phenotype with a gradually decreased number of functional alleles of paralogous genes. A gradually decreased number of functional Dlx5/6 alleles leads to a gradually worsened craniofacial morphogenesis [ 84 ]; gradually reduced Onecut1/Onecut2 alleles cause a dramatically reduced number of horizontal cells in the mouse retina [ 62 ]; a gradually decreased number of functional Hoxa10 , Hoxc10 , and Hoxd10 alleles results in gradually worsened kidney development [ 85 ]; and a decreased number of Lef / Tcf alleles gradually alters the specification and maintenance of epithelial progenitor cells [ 69 ]. The threshold level of functional alleles is specific for particular tissues and organs, and may differ for individual paralogous genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additive functions lead to a gradually worsened phenotype with a gradually decreased number of functional alleles of paralogous genes. A gradually decreased number of functional Dlx5/6 alleles leads to a gradually worsened craniofacial morphogenesis [ 84 ]; gradually reduced Onecut1/Onecut2 alleles cause a dramatically reduced number of horizontal cells in the mouse retina [ 62 ]; a gradually decreased number of functional Hoxa10 , Hoxc10 , and Hoxd10 alleles results in gradually worsened kidney development [ 85 ]; and a decreased number of Lef / Tcf alleles gradually alters the specification and maintenance of epithelial progenitor cells [ 69 ]. The threshold level of functional alleles is specific for particular tissues and organs, and may differ for individual paralogous genes.…”
Section: Discussionmentioning
confidence: 99%
“…A decline below the threshold level results in dramatic phenotypic consequences. The loss of more than one functional Dlx5/Dlx6 allele leads to alterations in pharyngeal patterning [ 84 ], a single Onecut1 / Onecut2 allele in any combination is not sufficient to prevent the complete loss of horizontal cells [ 62 ], less than three functional Hoxa10/Hoxc10/Hoxd10 alleles leads to defects during kidney development [ 85 ], and the presence of less than two out of the four Lef/Tcf transcription factors results in defects during lung development [ 69 ]. Additive functions were mostly observed for functionally equivalent paralogous genes, but non-equivalent paralogous genes may also exhibit additive functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our snATAC-seq motif analyses using the JASPAR and i-cisTarget databases 53,61 also show Onecut motif enrichment in the Convergence cluster. onecut is highly conserved and required for horizontal cell development in mice [62][63][64] . In Drosophila, we have found that onecut null mutants show age-related retinal dysmorphology with loss of PR rhabdomeres (to be reported elsewhere).…”
Section: Single Cell Regulatory Network Inference and Clustering (Sce...mentioning
confidence: 99%